2022
DOI: 10.1002/aenm.202201242
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Pb Management in Perovskite Solar Cells toward Eco‐Friendly Development

Abstract: of human society. Clean and green solar energy could be converted into electric energy through photovoltaic technologies. This can provide a green and sustainable way for energy utilization. [1][2][3] Inorganicorganic hybrid perovskite solar cells (PSCs) are considered to be one of the most promising photovoltaic applications, [4][5][6][7][8][9][10][11] owing to the favorable properties of perovskite materials, such as tunable bandgap, high absorption coefficient, large bipolar mobility, long carrier diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 184 publications
0
35
0
Order By: Relevance
“…Encapsulation has proved to be a simple and effective strategy to improve the external stability of PSCs by preventing the penetration of moisture and oxygen 55 57 and to prevent lead leakage 58 , which is a necessary part of commercialization.…”
Section: Resultsmentioning
confidence: 99%
“…Encapsulation has proved to be a simple and effective strategy to improve the external stability of PSCs by preventing the penetration of moisture and oxygen 55 57 and to prevent lead leakage 58 , which is a necessary part of commercialization.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, a variety of OHPs artificial synapses have been reported 10,[26][27][28][29][30] . In 2020, Pi et al reported an optically stimulated synaptic device based on the hybrid structure of silicon nanomembrane and perovskite, which has great potential in the field of multi-functional and low energy consumption synaptic devices [31][32][33] .However, the toxicity of lead and the intrinsic instability caused by the organic group in OHPs limit the further practical and commercial application of OHPs based artificial synapses in neuromorphic computing. Consequently, it is absolutely necessary to further explore non-or lowtoxicity and stable perovskite material to promote the commercial applications of perovskite artificial synapses 31,[34][35][36] .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is absolutely necessary to further explore the non-or low-toxicity and stable perovskite material to promote the commercial applications of perovskite artificial synapses. 31,[34][35][36] To solve this problem, large amounts of efforts such as Sn 2+ , Ge 2+ , Bi 3+ and Sb 3+ . [37][38][39][40] have been taken.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] With the rapid growth of the PV market, the global cumulative solar capacity reached about 773.2 GW in 2020. [ 21 ] If 1 GW of solar PV capacity using perovskite solar panels with an efficiency of ≈25% containing ≈3.5 tons of lead with a 0.5 μm thick Pb‐based perovskite layer, [ 22,23 ] the total amount of Pb contained in PSCs is ≈541 tons assuming only 20% of 773.2 GW PV market is occupied by perovskite solar panels. [ 21 ] Therefore, a sustainable strategy is an essential prerequisite to handling and disposing of Pb‐based perovskite materials to effectively mitigate the risk of Pb 2+ leakage.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Pb recycling methods were also developed to mitigate the environmental impacts of PSCs beyond their lifespan. Some recent reviews have provided one or some of the abovementioned aspects in Pb management of PSCs, [ 21,37,38 ] while a comprehensive review of Pb management of emerging Pb PVs is still lacking within the community. As a result, it is important to account for the development and provide insights for the environmental impact assessment, Pb 2+ leakage mitigation, and recycling toward their large‐scale commercialization.…”
Section: Introductionmentioning
confidence: 99%